Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Berpikir Kritis para Peserta Didik : Literatur Review: (The Influence of the Problem Based Learning Model on Students' Critical Thinking Ability: Literature Review) - Viona Delfiza, Milanda; Fuadiyah, Sa’diatul (BIODIK, 2024)
This literature research explores the role of education in creating quality human resources, with a focus on the importance of critical thinking skills in the context of biology learning. The aim of Indonesian national education is to develop the abilities, quality and dignity of human life. In this era of changing education systems, learning is expected to be student-centered with an emphasis on 4C skills, including critical thinking abilities. The importance of critical thinking skills in dealing with continuously flowing information is easy to realize, especially in the context of biology learning. However, there are still many challenges, such as the lack of conditions that support students to think critically and the perception of the difficulty of learning biology. One of the approaches proposed to improve students' critical thinking skills is through a problem-based learning model, especially Problem Based Learning (PBL). This research describes the results of analysis from various literature articles that support the effectiveness of PBL in improving students' critical thinking abilities. By hypothesis testing, homogeneity testing, and normality testing, this research concludes that the implementation of PBL significantly improves students' critical thinking skills. PBL stages, such as deductive reasoning, inductive reasoning, evaluation, analysis, and decision making, provide an effective framework in developing students' critical thinking skills. PBL emerged as an effective solution to improve students' critical thinking skills in biology learning. Implementation of this model not only provides opportunities for students to solve problems, but also encourages them to think analytically and be active in the learning process. This research provides empirical support for the positive role of PBL in overcoming the challenges of biology learning and advancing students' critical thinking skills. Abstrak. Penelitian literatur ini mengeksplorasi peran pendidikan dalam menciptakan sumber daya manusia yang berkualitas, dengan fokus pada pentingnya kemampuan berpikir kritis dalam konteks pembelajaran biologi. Tujuan pendidikan nasional Indonesia adalah mengembangkan kemampuan, mutu dan harkat dan martabat hidup manusia. Di era perubahan sistem pendidikan ini, pembelajaran diharapkan berpusat pada siswa dengan penekanan pada keterampilan 4C, termasuk kemampuan berpikir kritis. Pentingnya kemampuan berpikir kritis dalam menghadapi informasi yang terus mengalir mudah disadari, terutama dalam konteks pembelajaran biologi. Namun masih banyak tantangan yang dihadapi, seperti kurangnya kondisi yang mendukung siswa untuk berpikir kritis dan persepsi akan sulitnya pembelajaran biologi. Salah satu pendekatan yang diusulkan untuk meningkatkan kemampuan berpikir kritis siswa adalah melalui model pembelajaran berbasis masalah khususnya Problem Based Learning (PBL). Penelitian ini memaparkan hasil analisis dari berbagai artikel literatur yang mendukung efektivitas PBL dalam meningkatkan kemampuan berpikir kritis siswa. Melalui uji hipotesis, uji homogenitas, dan uji normalitas, penelitian ini menyimpulkan bahwa penerapan PBL secara signifikan meningkatkan keterampilan berpikir kritis siswa. Tahapan PBL seperti penalaran deduktif, penalaran induktif, evaluasi, analisis, dan pengambilan keputusan memberikan kerangka kerja yang efektif dalam mengembangkan kemampuan berpikir kritis siswa. PBL muncul sebagai solusi efektif untuk meningkatkan kemampuan berpikir kritis siswa dalam pembelajaran biologi. Penerapan model ini tidak hanya memberikan kesempatan kepada siswa untuk memecahkan masalah, tetapi juga mendorong mereka untuk berpikir analitis dan aktif dalam proses pembelajaran. Penelitian ini memberikan dukungan empiris terhadap peran positif PBL dalam mengatasi tantangan pembelajaran biologi dan meningkatkan kemampuan berpikir kritis siswa.